2014
DOI: 10.1002/jhet.1835
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Activities of Novel 2‐Alkylpyrrole Derivatives

Abstract: To investigate the alkyl analog of insecticide chlorfenapyr, two series of 2‐alkyl‐4‐bromo‐5‐(trifluoromethyl)pyrrole‐3‐carbonitriles were synthesized with a cycloaddition as the key step. The target products were characterized by 1H‐NMR spectroscopy, elemental analysis, or HRMS. The insecticidal, herbicidal, and antifungal activities of the target compounds were evaluated and found that these compounds did not show much insecticidal activity, but compounds 4, 10, and 11 had very good fungicidal activities aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…This result indicated that oxazolone might be an intermediate for the formation of pyrrole. The [3 + 2] cycloaddition of oxazolones with electron-deficient alkenes usually leads to two regioisomers, and the product with the substituent near the “anionic” atom (carbonyl α-carbon substituted by the R 1 group) was predominant according to the frontier orbital analysis . However, in this work, highly reversed regioselectivity was observed in all cases, regardless of the electronic nature and the size of the R 1 and R 2 groups.…”
Section: Results and Discussionmentioning
confidence: 56%
“…This result indicated that oxazolone might be an intermediate for the formation of pyrrole. The [3 + 2] cycloaddition of oxazolones with electron-deficient alkenes usually leads to two regioisomers, and the product with the substituent near the “anionic” atom (carbonyl α-carbon substituted by the R 1 group) was predominant according to the frontier orbital analysis . However, in this work, highly reversed regioselectivity was observed in all cases, regardless of the electronic nature and the size of the R 1 and R 2 groups.…”
Section: Results and Discussionmentioning
confidence: 56%
“…Such a compound was identified as a secondary metabolite of Streptomyces griseus , considered the main bioactive compound against the oomycete Phytophthora capsici [ 7 ]. On the other hand, a series of 2-alkyl-4-bromo-5-(trifluoromethyl)pyrrole-3-carbonitriles was obtained having excellent fungicidal activities against Alternaria solani and Fusarium oxysporum [ 8 ]. Substituted 3,4-dimethyl-1 H -pyrrole-2-carboxamides and carbohydrazide analogues could be considered potential antifungal and antimicrobial agents, especially against the pathogen Aspergillus niger [ 9 ].…”
Section: Introductionmentioning
confidence: 99%